Time-delay stability analysis for hybrid energy storage system with hierarchical control in DC microgrids - Dong, Chaoyu (2020)
Hybrid energy storage system (HESS) plays an important role in the operation of dc microgrids which have attracted significant research attention recently. The hierarchical control is widely adopted for the coordination of multiple energy storages in a HESS. As the hierarchical control comprises the centralized and the decentralized control levels, the time delays during signal transfer processes between two control levels may significantly affect HESS operation and may lead to instability. In this paper, considering the multiple delays in the hierarchical control processes, the maximum delayed time (MDT) is defined to assess the stability margin for a HESS. An accurate and effective method based on small signal stability model is then proposed to determine the MDT of a HESS to maintain its stability. The effectiveness and correctness of the proposed method are verified using a lab-scale dc microgrid.